2013
DOI: 10.1371/journal.pone.0063871
|View full text |Cite
|
Sign up to set email alerts
|

VBP15, a Glucocorticoid Analogue, Is Effective at Reducing Allergic Lung Inflammation in Mice

Abstract: Asthma is a chronic inflammatory condition of the lower respiratory tract associated with airway hyperreactivity and mucus obstruction in which a majority of cases are due to an allergic response to environmental allergens. Glucocorticoids such as prednisone have been standard treatment for many inflammatory diseases for the past 60 years. However, despite their effectiveness, long-term treatment is often limited by adverse side effects believed to be caused by glucocorticoid receptor-mediated gene transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…We have previously shown that chronic VBP15 treatment does not affect bone growth in vivo [20,21]. Thus, we determined whether or not extended VBP15 treatment could result in reduced body length by treating young outbred wild type mice (12 days of age) daily for 5 weeks.…”
Section: Vbp15 Treatment Results In Less Growth Stunting In Vivomentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that chronic VBP15 treatment does not affect bone growth in vivo [20,21]. Thus, we determined whether or not extended VBP15 treatment could result in reduced body length by treating young outbred wild type mice (12 days of age) daily for 5 weeks.…”
Section: Vbp15 Treatment Results In Less Growth Stunting In Vivomentioning
confidence: 99%
“…VBP15 is an anti-inflammatory compound that has been shown to be an effective inhibitor of NFjB activity both in vitro and in vivo [19][20][21][22] but does not induce the GREmediated transcription (genomic transactivation property) believed to be responsible for many of the detrimental metabolic side effects of glucocorticoids [19,21]. In the current study, VBP15 inhibited the production of pro-inflammatory cytokines IL-6 and IL-8, as well as chemokine, CCL5, in TNFa-stimulated human intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VBP15 shows strong anti-inflammatory activities with potent inhibition of NFjB activity both in vitro and in vivo Damsker et al 2013;Heier et al 2013). Side effect profiles of VBP15 are also reduced, through selective loss of the GRE-mediated transactivation properties of glucocorticoids Heier et al 2013).…”
Section: Introductionmentioning
confidence: 99%